(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2012)
The objective of the present investigation was to develop bilayered tablets of lornoxicam to achieve biphasic release pattern. A bilayered tablet, consisting of an immediate and controlled release layer, was prepared by direct compression technique. The controlled release effect was achieved by using various hydrophilic natural, semi synthetic and synthetic controlled release polymers such as xanthan gum, hydroxypropyl methylcellulose (HPMC) and polyethylene oxide (PEO) to modulate the release of the drug. The in vitro drug release profiles showed the biphasic release behavior in which the immediate release (IR) layer containing the lornoxicam was released within 15 minutes, whereas the controlled release (CR) layer controlled the drug release for up to 24 h. All the bilayered tablets formulated have followed the zero order release with non-Fickian diffusion controlled release mechanism after the initial burst release. FTIR studies revealed that there was no interaction between the drug and polymers used in the study. Statistical analysis (ANOVA) showed no significant difference in the cumulative amount of drug release after 15 min, but significant difference (p < 0.05) in the amount of drug released after 24 h from optimized formulations was observed. Based on the release kinetic parameters obtained, it can be concluded that xanthan gum polymer was suitable for providing a biphasic release of lornoxicam.